2008
DOI: 10.1038/emboj.2008.112
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Cyk-4 binding to ECT2 and FIP3 regulates cleavage furrow ingression and abscission during cytokinesis

Abstract: Cytokinesis is a highly regulated and dynamic event that involves the reorganization of the cytoskeleton and membrane compartments. Recently, FIP3 has been implicated in targeting of recycling endosomes to the mid-body of dividing cells and is found required for abscission. Here, we demonstrate that the centralspindlin component Cyk-4 is a FIP3-binding protein. Furthermore, we show that FIP3 binds to Cyk-4 at late telophase and that centralspindlin may be required for FIP3 recruitment to the mid-body. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 47 publications
8
97
0
1
Order By: Relevance
“…The FIP3-binding region on CYK-4 overlaps with the ECT2-binding domain. FIP3 and ECT2 form exclusive complexes with CYK-4 and removal of ECT2 from the centraspindlin complex at late telophase is required for the recruitment of FIP3-containing endosomes to the cleavage furrow [25]. Another important protein of this complex is PLK1 (polo-like kinase 1) which binds to microtubules and interacts with MKLP2.…”
Section: Early Cytokinesismentioning
confidence: 99%
See 1 more Smart Citation
“…The FIP3-binding region on CYK-4 overlaps with the ECT2-binding domain. FIP3 and ECT2 form exclusive complexes with CYK-4 and removal of ECT2 from the centraspindlin complex at late telophase is required for the recruitment of FIP3-containing endosomes to the cleavage furrow [25]. Another important protein of this complex is PLK1 (polo-like kinase 1) which binds to microtubules and interacts with MKLP2.…”
Section: Early Cytokinesismentioning
confidence: 99%
“…Microtubule-associated proteins PRC1 [13,14] Centralspindlin complex CYK-4 [2,15] MKLP1 [2,15] Chromosome passenger complex INCENP [16,17] Survinin [16,17] Borealin [16,17] Aurora B [16,17] ESRCTs and associated proteins CEP55 [30][31][32] TSG101 [31,32] ALIX [31,32] CHMP1B [33] Spastin [33] CHMP4B [31,32,34] FYVE-CENT [34] TTC19 [34] Kinesins KIF4A [14] MKLP2 [17] MPP1 [22] KIF14 [23] KIF13A [34] Additional proteins NuSAP [18] Orbit [19] ASP [20] TBCD [21] ECT2 [24] FIP3 [25] PLK1 [26,27] Septins [28] Anillin [29] during anaphase and cytokinesis and is important for the last step of abscission. CEP55 binds directly MKLP1 and is controlled by centralspindlin, since knockdown of centralspindlin abolishes CEP55 from the midbody [30].…”
Section: The Abscission Step Of Cytokinesismentioning
confidence: 99%
“…In late telophase, CEP55, an adaptor protein that is essential for midbody recruitment of the endosomal sorting complex required for transport (ESCRT) proteins (Caballe and Martin-Serrano, 2011), localises to the Flemming body by directly interacting with MKLP1 in a manner that is negatively regulated by PLK1-mediated phosphorylation (Bastos and Barr, 2010;Zhao et al, 2006). FIP3, another adaptor protein that interacts with Arf6 and Rab11 GTPases, competes with ECT2 for CYK4 binding and localises to the Flemming body as ECT2 leaves in late telophase (Simon et al, 2008). Interaction between Arf6 and MKLP1 is important for post-mitotic stable maintenance of the midbody and for successful abscission (Makyio et al, 2012;Joseph et al, 2012).…”
Section: Interactions Between Midzone Organisers and Their Upstream Amentioning
confidence: 99%
“…Pebble, the Drosophila homolog of GEF ECT2, is critical for cytokinesis (Yüce et al 2005;Simon et al 2008;Wolfe et al 2009), interacts with RacGAP50C (O' Keefe et al 2001;Somers and Saint 2003), and activates RhoA. Indeed, we found that Centralspindlin downstream effectors Rho1 (RhoA) and Sticky (Citron kinase) are required for accurate meiotic chromosome segregation.…”
Section: Mitotic Spindle Midzone Proteins Regulate Acentrosomal Spindmentioning
confidence: 68%
“…The role of the Centralspindlin proteins in mitotic spindle midzone formation and stabilization leading to cytokinesis is well documented (Guse et al 2005;D'Avino et al 2006;Pavicic-Kaltenbrunner et al 2007;Simon et al 2008). Their contribution to acentrosomal spindle assembly, however, has not been characterized.…”
Section: Antibodies and Immunofluorescent Microscopymentioning
confidence: 99%